О взглядах поляков на участие государства в экономике - Чарник, Ш. (Социология: теория, методы, маркетинг, 2005)
Based on the public opinion research conducted in the last ten year period one can
distinguish two opposite processes in the public consciousness of the Poles as regards
economy functioning, free market and desirable role of state in economic processes.
On the one hand it may be observed how the society is gradually adapting to the main
elements of capitalist Social order (private enterprise ownership, market price
regulation, etc). On the other hand we can see a progressive rehabilitation of socialism
and strengthening positions of economic egalitarism.